Calculating the Binding Energy of Nucleus (3H – 12C ) by finding the Numerical Solutions of Faddeev's Equation, using Three Nucleon Forces (Latakia University Journal -Basic Sciences Series, 2019)
We investigate the effect of introducing the three nucleon forces on calculating the binding energy of Tritium and Carbon 12, where the two nucleon force has only  assigned binding energy less value than the experimental one, and this is called the shifting energy problem. Many interpretations have been put forward to handle this problem. In this paper, we show that the introduction of three nucleon forces produces the correct binding energy of Tritium and Carbon-12. We start by using the Faddeev equations for forming a three-body system in configuration space in the total angular momentum representation, solving them by using numerical methods over two stages: the first is interpolating the unknown wave function by splint method; the second is using  the linear algebra technique, which is called the Lanczos method for obtaining  specific values. We consider the nuclei of carbon as a cluster of three nuclei of alpha, and this model has given positive  results.